Industrial electricity & motor controls - Miller, Rex, 1929-; Miller, Mark R. (New York : McGraw-Hill, 2008)
'Industrial Electricity and Motor Controls' is a complete guide to electrical field and its equipment, including troubleshooting and repair. Electricity and electronics are introduced, thoroughly explained, and used to analyse and solve problems common to industrial electrical equipment such as motors and controls.
Tools and equipment -- Safety in the workplace -- Symbols -- Control circuits and diagrams -- Switches -- Magnetism and solenoids -- Relays -- Electric motors -- Timers and sensors -- Sensors and sensing -- Solenoids and valves -- Motor starting methods -- Solid-state reduced-voltage starters -- Speed control and monitoring -- Motor control and protection -- Three-phase controllers -- Drives -- Transformers -- Power generation -- Power distribution systems -- Programmable controllers -- Troubleshooting and maintenance -- Careers in electricity.
Includes bibliographical references and index.
Keywords: Electric machinery; Industrial electronics; Electric motors -- Electronic control